2014
DOI: 10.1371/journal.pone.0085945
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Levels of Plasma Phenylalanine in Schizophrenia: A Guanosine Triphosphate Cyclohydrolase-1 Metabolic Pathway Abnormality?

Abstract: BackgroundPhenylalanine and tyrosine are precursor amino acids required for the synthesis of dopamine, the main neurotransmitter implicated in the neurobiology of schizophrenia. Inflammation, increasingly implicated in schizophrenia, can impair the function of the enzyme Phenylalanine hydroxylase (PAH; which catalyzes the conversion of phenylalanine to tyrosine) and thus lead to elevated phenylalanine levels and reduced tyrosine levels. This study aimed to compare phenylalanine, tyrosine, and their ratio (a pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 34 publications
1
15
0
Order By: Relevance
“…We have previously reported that Phe levels and Phe:Tyr ratio were elevated in the same cohort of patients with schizophrenia when compared with controls (40). To our knowledge, there have been no studies investigating links between blood levels of molecular precursors of dopamine and serotonin in relationship to smoking in patients with schizophrenia.…”
Section: Introductionmentioning
confidence: 84%
“…We have previously reported that Phe levels and Phe:Tyr ratio were elevated in the same cohort of patients with schizophrenia when compared with controls (40). To our knowledge, there have been no studies investigating links between blood levels of molecular precursors of dopamine and serotonin in relationship to smoking in patients with schizophrenia.…”
Section: Introductionmentioning
confidence: 84%
“…Using high performance liquid chromatography (HPLC), plasma phenylalanine and tyrosine levels were measured using 3-nitro-L-tyrosine as an internal standard as described elsewhere [84, 89]. …”
Section: Methodsmentioning
confidence: 99%
“…BH4 is involved in the production of various neurotransmitters including serotonin, dopamine, epinephrine, and norepinephrine and is vital in nitric oxide (NO) production (Richardson et al, 2007;Werner et al, 2011). Deficiency in BH4 has been associated to SCZ (Richardson et al, 2005, Okusaga et al, 2014, Milstien and Katusic, 1999. In the likely context of astrocyte activation during early neurodevelopmental, post-transcriptionally regulatory mutations along PCBD2 could have an important role in BH4 synthesis and regeneration pathway, causing damaging disturbances in the mentioned processes.…”
Section: Accepted Manuscriptmentioning
confidence: 99%